Using Group Discussions to Hone 21st-Century Skills in Teaching Political English - A. S. Rodomanchenko; K. A. Vertlib (Дискурс профессиональной коммуникации, 2024)
In the era of globalization and digitalization, the importance of 21st-century skills—such as communication, collaboration, creativity, and critical thinking—has significantly increased. To prepare students for contemporary challenges, educators must focus on tasks that develop these essential skills and competencies. This article explores the use of debates and ‘discussion brackets’—a novel group discussion format in EFL methodology—to foster 21st-century skills among undergraduates in non-linguistic programs. The authors conducted extensive research on the concept of 21st-century skills and examined how it aligns with the Russian concepts of “competences” and “skills.” The study aims to uncover the potential of discussion brackets in skill development. A review of the literature revealed scant information on the effectiveness of this discussion format, leading to the hypothesis that discussion brackets, alongside debates, could effectively develop key 21st-century competencies. An experiment was carried out with first-year students of the double degree program in Economics and Politics in Asia at the National Research University Higher School of Economics and Kyung Hee University, as part of an EFL course titled “English for Political Studies.” The teacher employed specific criteria to assess students’ engagement in discussion brackets and debates, evaluating their competency development. Subsequent to the activities, students completed a survey with self-reflection questions based on the Likert scale and participated in an oral interview. The results indicate that active participation in both tasks enabled students to enhance their mastery of 21st-century skills. Students reported improved critical thinking and the ability to think creatively. Furthermore, the introduction of discussion brackets sparked immediate interest and engagement among the students.